COVID-19 and Anemia: What Do We Know So Far? - Luai Abu-Ismail (10712857) (2023)
On 11 March 2020, the World Health Organization (WHO) declared the novel SARS-CoV-2 virus responsible for causing COVID-19, a global pandemic. The virus primarily targets the respiratory system but can also affect other systems, notably causing hematological pathologies. Anemia, a common hematologic disorder, is characterized by the reduced oxygen-carrying capacity of red blood cells. The existing literature has a suspected link between anemia and severe COVID-19 cases. Researchers are currently investigating the long-term complications of COVID-19 in anemic patients, as these complications may play a crucial role in predicting patient prognosis. Anemic individuals are at a higher risk of experiencing severe COVID-19 infections due to several contributing pathophysiological mechanisms, including thrombotic, hemorrhagic, and autoimmune etiologies. The primary effect of these mechanisms is a decrease in circulating hemoglobin levels, reducing oxygen availability for cells. This exacerbates the hypoxia caused by COVID-19-induced acute respiratory distress syndrome (ARDS). This review offers a comprehensive overview of the evidence regarding the long-term complications of COVID-19 in anemic patients. Other Information Published in: Hemoglobin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/03630269.2023.2236546